Makna Filosofis Panjang Tong Dipotong Pondok Tong Disambung sebagai Prinsip Budaya Kampung Adat Cikondang - Putri Ardila; Dirham Alkayyisa Tayyara Tazkia; Gadies Reva Dhea M; Ghea Amanda Cahaya Puspa; Syalaisya Namira; Mamat Supriatna; Aam Imaduddin (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In an effort to understand the richness of local culture that continues to survive amid the tides of changing times, this study examines the philosophical meaning of the traditional expression Panjang Tong Dipotong, Pondok Tong Disambung as a foundational value in cultural preservation in the Cikondang Indigenous Village. This research aims to reveal how this philosophy is applied in the daily lives of the community and its role in maintaining cultural continuity. The study was conducted using a qualitative method with an ethnographic approach, and data were collected through in-depth interviews with several informants from the Cikondang Indigenous Village community. The findings show that the expression is not only a symbol of tradition but also serves as a guiding principle that preserves cultural heritage in an intact and adaptive manner amidst the forces of globalization and modernization.